Materials and Installation of Delivery Pipes for Irrigation Systems - Brian Boman; Sanjay Shukla (EDIS)
This document, Cir 1424, is one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date February 2001.